1998
DOI: 10.1016/s0002-9440(10)65751-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Muscle Degeneration in the δ-Sarcoglycan-Deficient Hamster

Abstract: The BIO14.6 hamster is an extensively used animal model of autosomal recessive cardiomyopathy and muscular dystrophy. Recently, a large deletion in the 5' end of the delta-sarcoglycan gene was found to be the primary genetic defect in the hamster. In the present investigation, we studied the effects of the delta-sarcoglycan deletion on transcription, expression, and function of the dystrophin-glycoprotein complex in skeletal and cardiac muscle. We demonstrated that in striated muscle the genetic defect leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 47 publications
4
92
1
3
Order By: Relevance
“…Male F1B control and BIO14.6 cardiomyopathic hamsters were obtained from BioBreeders (Fitchburg, MA). A colony of ␦-sarcoglycan-deficient hamsters (28) and Sgca-deficient mice (10) was established at the University of Iowa. All animal studies were authorized by the Animal Care Use and Review Committee of the University of Iowa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male F1B control and BIO14.6 cardiomyopathic hamsters were obtained from BioBreeders (Fitchburg, MA). A colony of ␦-sarcoglycan-deficient hamsters (28) and Sgca-deficient mice (10) was established at the University of Iowa. All animal studies were authorized by the Animal Care Use and Review Committee of the University of Iowa.…”
Section: Methodsmentioning
confidence: 99%
“…The cardiomyopathic hamster is a widely studied animal model for sarcoglycan deficiency that has a primary mutation in the ␦-sarcoglycan gene (28,38). If ␦-and ⑀-sarcoglycan are both components of the sarcoglycan complex in smooth muscle cells, the null mutation in the ␦-sarcoglycan might affect the distribution of ⑀-sarcoglycan.…”
Section: Distribution Of ⑀-Sarcoglycan In Smoothmentioning
confidence: 99%
“…A primary mutation in any one of the SG genes leads to concomitant reduction of the entire SG complex. The exact function of the SGsarcospan complex is still unknown, but some putative functions have been proposed; it may stabilize the DGC components in the muscle membrane Straub et al 1998); it may regulate localization of c-filamin (Thompson et al 2000). Using animal models and virus-gene transfer techniques, it has been demonstrated that genetic deficiencies of the SG complex can be corrected in vivo Durbeej et al 2003).…”
Section: Dgc and Muscular Dystrophymentioning
confidence: 99%
“…muscular dystrophy | eccentric contraction | titin | skeletal muscle | dystroglycan M uscular dystrophies are a heterogenous group of genetic disorders characterized by progressive muscle weakness and wasting (1,2). Mutations in genes encoding proteins of the dystrophin-glycoprotein complex (DGC) are associated with various muscular dystrophies (3)(4)(5)(6)(7)(8)(9)(10). The DGC is a multimeric complex comprising both transmembrane proteins [β-dystroglycan (DG), sarcoglycans (α, β, γ, and δ), and sarcospan] and membrane-associated proteins (α-DG, dystrophin, syntrophin, dystrobrevin, and neuronal nitric oxide synthase).…”
mentioning
confidence: 99%
“…The extracellular matrix receptor function of α-DG is impaired when either DAG1 is itself mutated (limb-girdle muscular dystrophy type 2P) (10,16,17) or genes that encode putative or known glycosyltransferases that act on α-DG are mutated (Walker-Warburg syndrome, muscle-eye-brain disease, Fukuyama congenital muscular dystrophy, congenital muscular dystrophy types 1C and 1D, or limb-girdle muscular dystrophy) (12,18,19). Sarcolemmal expression of α-DG, sarcospan, and the sarcoglycan complex is reduced in patients with distinct sarcoglycan mutations (limb-girdle muscular dystrophy type 2C-F) (3)(4)(5)20). Levels of α-DG, β-DG, the sarcoglycan complex, and sarcospan are reduced at the sarcolemma of patients with dystrophin mutations (Duchenne and Becker muscular dystrophy) (6)(7)(8)(9).…”
mentioning
confidence: 99%